Joint Solution for the Online 3D Photorealistic Mapping Using SfM and SLAM. (4th January 2013) - Choi, Hyunga; Jun, ChangHyun; Li Yuen, Shang; Cho, HyunGi; Doh, Nakju Lett
This paper proposes a novel hybrid solution of SfM (Structure from Motion) and SLAM (Simultaneous Localization And Mapping) for the online generation of a 3D photorealistic map. As it is well known, the SfM can generate a 3D photo map, but it is difficult to get the real-scale as well as to build an online map (i.e., the map cannot be generated on the fly). In contrast, while SLAM frameworks are suitable for online real-scale mapping, they are not adequate for 3D photo map generation. To create a synergy effect, the proposed method combines SfM and SLAM. The way of combination is to use SfM for the generation of local maps and to utilize SLAM for a fusion of local maps in a globally consistent manner. Experimental results show that the proposed hybrid approach enables online 3D photorealistic mapping.